The influence of cavity preparation and press-fit cup implantation on restoring the hip rotation center. (March 2019) - Messer-Hannemann, Philipp; Bätz, Johanna; Lampe, Frank; Klein, Anke; Püschel, Klaus; Campbell, Graeme M.; Morlock, Michael
Abstract: Background: Reaming of the acetabular cavity and cup implantation directly influence the hip rotation center and contact area between implant and bone. Previous studies have reported on an altered rotation center after total hip arthroplasty, but have not studied the influence of reaming and cup implantation separately. Aim of this study was therefore to analyze the individual influence of acetabular reaming and subsequent cup implantation on the rotation center and how this influences the contact conditions at the bone-implant interface. Methods: Acetabular press-fit cups were implanted into the left and right hips of three full cadavers ( n = 6). CT scans were performed to calculate the change in hip rotation center after reaming and prior to liner insertion. 3D models of the cups were used to determine the polar gap, the contact conditions and the effective press-fit. Findings: Reaming the acetabular cavity shifted the rotation center medially (median 5.8 mm, range 4.8–9.1), superiorly (5.3 mm, 3.0–7.0) and posteriorly (2.9 mm, 1.0–5.3). With cup implantation, the rotation center shifted back towards the native position, but no full restoration was observed. The degree of shift increased with the size of polar gap (rs = 0.829, P = .042), which inversely reduced the contact area (rs = 0.886, P = .019). Interpretation: This study reveals that the dominant factor in hip rotation center restoration is the reaming process, while the cup implantation for a given nominal press-fit has only a small influence. Increasing the press-fit would improve the restoration but bares the danger of insufficient bone coverage and periprosthetic fractures due to the high forces needed. Highlights: Acetabular reaming is the dominant factor to restore the hip rotation center. Acetabular reaming shifts the hip rotation center away from its native position. No full restoration of the altered rotation center achieved with cup implantation. Restoration of the hip rotation center is dependent on cup seating and press-fit. Medialization during acetabular reaming tended to increase implant bone coverage.